Prevalence of otitis media and risk factors for sensorineural hearing loss among infants attending routine well-baby clinics in urban and rural/remote Samoa: a study protocol - Annette Kaspar; Sione Pifeleti; Carlie Driscoll (Journal of Global Health Reports)
# Background The World Health Organization recommends newborn and infant hearing screening programs for all member states to enable early detection and intervention for children with hearing loss. Ear and hearing services are limited in the Pacific Islands, a region with one of the highest global rates of ear disease and hearing loss. Given that a significant proportion of childhood hearing loss is preventable through public health measures, collaboration with existing primary and public health platforms should reduce the prevalence of avoidable ear and hearing disorders among infants and young children. Previous work has investigated an infant ear and hearing program for child welfare clinics in an urban Pacific Island setting. The present study will build on this previous work by investigating the possibility of an Infant Ear and Hearing Program in a different Pacific Island country, and performing comparisons between urban and rural/remote populations.